Global warming and monsoon climate (MAUSAM, 2001)
The response of the Asian summer monsoon to transient increases of greenhouse gases (GHGs) and sulfate aerosols in the Earth's atmosphere is examined using the data generated in numerical experiments with available coupled atmosphere-ocean global climate models (A-O GCMs). A comparison of observed and model-simulated trends in monthly mean near-surface temperature and rainfall over the region provides evidence of skill of the A-O GCMs in simulating the regional climatology. The potential role of the sulfate aerosols in obscuring the GHG- induced warming over the Indian subcontinent is discussed. Even though the simulated total seasonal rainfall over the Indian subcontinent during summer monsoon season is underestimated in most of the A-O GCMs, the year to year variability in simulated monsoon rainfall over the study region is found to be in fair agreement with the observed climatology.